Fossil Fishes from the Marine Late Palaeozoic of Holm-Amdrup Land, North-East Greenland. - Bendix-Almgreen, Svend Erik (Meddelelser om Grønland, 1975)
This paper presents morphological descriptions and comparisons of some late Palaeozoic fish remains, more precisely teeth, scales and a single fin-spine representing selachians (Ctenacanthus sp. and ’Cladodus’ sp.), durophagous elasmobranchs (Lagarodus sp., Petalodus sp., ’Helodus’sp . and a cochliodontid or menaspid representative), and a single actinopterygian (Acrolepis? sp.). The material originates from Upper Carboniferous (Moscovian) and Lower Permian marine deposits constituting the socalled ’Lower Marine group’ and ’Upper Marine group’ of Holm Land and Amdrup Land (80°-81 °) in North-East Greenland. The collection comprises two faunal assemblages which, being the northernmost of their kind and age yet found, are biostratigraphically evaluated on the basis of comparisons with broadly contemporaneous fish faunal material from Europe (particularly the U.S.S.R.) and from North America. The palaeontological evidence presented, including certain aspects of the author’s recent investigations of new Heliocoprion material from Arctic Canada, indicates rather conclusively a late Lower Permian (perhaps Roadian) age for the uppermost part of the ’Upper Marine group’. It is concluded that this part of the Holm Land - Amdrup Land marine sequence can be broadly correlated with: 1) The Assistance Formation of Arctic Canada, 2) the Meade Peak Member of the middle Phosphoria Formation of western U.S.A., and 3) the Brachiopod Cherts of western Spitsbergen. On basis of chronostratigraphical evidence a broad correlation of the Holm Land - Amdrup Land marine sequence and the late Palaeozoic continental Mesters Vig Formation of central East Greenland is attempted. A final short comment concerns changes in composition between the elasmobranch assemblage from the late Lower Permian of Amdrup Land, as now known, and the richly varied fauna found in the Upper Permian (Araksian) Foldvik Creek Formation of central East Greenland.